Elementary school Physical Education, Sports, and Health teachers' understanding of the implementation of Kurikulum Merdeka - Rifki Hidayat; Sri Widaningsih; Henry Asmara (Inovasi Kurikulum, 2026)
Kurikulum Merdeka has been mandated for implementation in all schools; however, its application continues to face various challenges, particularly related to teachers’ understanding, especially within the madrasah context. This study aims to describe the cognitive understanding of Physical Education, Sports, and Health (Pendidikan Jasmani, Olahraga, dan Kesehatan or PJOK) teachers in Madrasah Ibtidaiyah regarding the Kurikulum Merdeka. The research was conducted at a Madrasah Ibtidaiyah in Paseh District, Bandung Regency, employing a qualitative case study approach. Six PJOK teachers were selected as research participants through purposive sampling. Data were collected through observations, semi-structured interviews, and documentation, and analyzed descriptively. The findings indicate that teachers’ cognitive understanding of the Kurikulum Merdeka in PJOK varies, encompassing abilities to explain, interpret, summarize, classify, and compare learning concepts in accordance with curriculum principles. Some teachers demonstrate adequate competence in interpreting learning outcomes and adapting learning activities to students’ needs, whereas others experience difficulties with lesson planning and accessing professional development. This study highlights the importance of continuous professional development and the strengthening of teacher discussion forums, such as PJOK Teacher Working Groups, to support more effective implementation of the Kurikulum Merdeka in madrasah settings.   Abstrak Implementasi kurikulum merdeka perlu ada di semua sekolah. Namun dalam proses implementasinya masih banyak tantangan, salah satunya adalah terkait pemahaman guru terhadap proses implementasi dengan baik di lapangan, khususnya di lingkungan madrasah. Penelitian ini bertujuan untuk mendeskripsikan pemahaman guru Pendidikan Jasmani, Olahraga, dan Kesehatan (PJOK) Madrasah Ibtidaiyah (MI) dalam pelaksanaan Kurikulum Merdeka, khususnya dalam ranah kognitif. Penelitian dilakukan di MI Kecamatan Paseh, Kabupaten Bandung dengan menggunakan pendekatan kualitatif dan metode studi kasus. Subjek penelitian ini adalah enam guru PJOK yang dipilih melalui teknik purposif sampling. Teknik pengumpulan data meliputi observasi, wawancara semi-terstruktur, dan dokumentasi. Hasil penelitian menunjukkan bahwa pemahaman guru PJOK dalam ranah kognitif Kurikulum Merdeka sangat bervariasi, termasuk kemampuan menjelaskan, menafsirkan, meringkas, mengklasifikasikan, dan membandingkan konsep pembelajaran PJOK belum sesuai dengan prinsip-prinsip Kurikulum Merdeka. Beberapa guru mampu memaknai capaian pembelajaran dengan baik dan menyesuaikan kegiatan pembelajaran sesuai dengan kebutuhan murid, namun masih ada guru yang belum bisa penyusunan rencana pembelajaran dan adanya keterbatasan pelatihan guru PJOK. Penelitian ini merekomendasikan pentingnya pelatihan berkelanjutan dan pembentukan forum diskusi seperti Kelompok Kerja Guru khusus PJOK agar implementasi Kurikulum Merdeka berjalan lebih optimal. Kata Kunci: madrasah ibtidaiyah; Kurikulum Merdeka; PJOK; pemahaman guru